"Green Fluff"? The Role of Corporate Sustainability Initiatives in Effective Climate Policy: Comment on "Science‐Based Carbon Targets for the Corporate World: The Ultimate Sustainability Commitment, or a Costly Distraction?". (2nd September 2015) - Marland, Gregg; Kowalczyk, Tammy; Cherry, Todd L.
Abstract : The commentary by Schendler and Trexler (2015) strikes us as an intriguing paradox. Schendler and Trexler see responses to the threat of global climate change beginning to move forward in the corporate world, but they fear these corporate initiatives will be a distraction from what is ultimately required. They emphasize the need for "greater government intervention." An earlier text by Schendler and Toffel (2013) notes, and we agree, that "we're failing to deal with the problem at anywhere near sufficient scale." But we feel that the article by Schendler and Trexler does not adequately acknowledge the importance of these corporate efforts as elements of initiation and leadership. Schendler and Trexler express the impatience that many of us feel regarding the continued failure of political progress at the national and international levels. But they do not embrace the thoughts attributed to the sixth century B.C. Chinese philosopher Lao Tzu: "A journey of a thousand miles begins with a single step." They fail to acknowledge that, in democratic governments, there is the need for grass‐roots support in order to develop and implement effective policy. Rather than distractions, individual and corporate efforts are generally necessary prerequisites for implementation of and receptiveness to government action. We agree that society is not dealing with climate change at anything approaching the needed scale and that, ultimately, a meaningful government and international response to climate change is required. The challenge is finding the way forward to achieve this outcome. In a first‐best scenario, the global community would simply negotiate an effective international climate agreement. For more than 35 years, individual countries have collaborated to pursue this first‐best scenario, starting with the first World Climate Conference in 1979 and continuing with the United Nations Framework Convention on Climate Change (UNFCCC) and the Kyoto Protocol. But this "top‐down" approach has yielded little success and even less hope, with global carbon dioxide (CO2 ) emissions increasing by more than 50% since adoption of the UNFCCC in 1992. While countries agree on the need for an international agreement, "there is disagreement on almost every aspect of the climate change problem. Countries approach the problem in different stages of development and from different development paths, and thus with different perspectives" (Cherry et al. 2014, 23).